Heterophase states in ferroelectric solid solutions of sodium, potassium and cadmium niobates - M. O. Moysa; V. Yu. Topolov; L. A. Shilkina; K. P. Andryushin; L. A. Reznichenko (Journal of Advanced Dielectrics)
An analysis of heterophase states was carried out for ferro-active solid solutions of the system ([Formula: see text])NaNbO[Formula: see text]KNbO[Formula: see text]CdNb2O6. A complete stress relief at interfaces between phases in solid solutions with [Formula: see text] and [Formula: see text], 0.40, and 0.45 is realized at the single-domain state of the tetragonal and orthorhombic phases. In solid solutions with [Formula: see text] and [Formula: see text] and 0.20, as well as with [Formula: see text] and 0.10, and [Formula: see text], the formation of a planar interphase boundary being parallel to a zero-net-strain plane occurs at the elastic matching of the single-domain tetragonal and polydomain orthorhombic phases. In contrast to this, at [Formula: see text] and [Formula: see text], 0.30, and 0.35, the complete stress relief is associated with a co-existence of the single-domain orthorhombic and polydomain tetragonal phases, however in some cases, the tetragonal phase aims at a monodomainization.